Political Institutions, State Building, and Tax Capacity : Crossing the Tipping Point - Gaspar, Vitor (IMF Working Papers; Working Paper, 2016)
An empirical finding by Gaspar, Jaramillo and Wingender (2016) shows that once countries cross a tax-to-GDP threshold of around 12 3/4 percent, real GDP per capita increases sharply and in a sustained manner over the following decade. In this paper, we attempt via four case studies-Spain, China, Colombia, and Nigeria-to illustrate that the improvements in tax capacity have been part of a deeper process of state capacity building. We discuss the political conditions that supported tax capacity building, highlighting three important political ingredients: constitutive institutions, inclusive politics and credible leadership.